A polarographic study : the estimation of sodium and potassium in the presence of each other - Carter, Austin John (Rhodes University, Faculty of Science, Department of Chemistry, 1938)
The polarographic method has been described, and an attempt made to describe the difficulty of the simultaneous deposition of sodium and potassium. Various methods have been examined, of which precipitation of potassium with magnesium dipicrylaminate seems the most promising. The quantitative results were unsatisfactory, and possible sources of error are discussed. The method, while very convenient, rapid and labour-saving, is not sufficiently standardised to be trustworthy.
Keywords: Polarographs; Polarography; Potassium; Sodium